Where Students With the Most Significant Cognitive Disabilities Are Taught: Implications for General Curriculum Access. (April 2015) - Kleinert, Harold; Towles-Reeves, Elizabeth; Quenemoen, Rachel; Thurlow, Martha; Fluegge, Lauren; Weseman, Laura; Kerbel, Allison
Surveying 15 states and 39, 837 students, this study examined the extent to which students who took an alternate assessment based on alternate achievement standards in the 2010–2011 school year had access to regular education settings and the extent to which that access correlated with expressive communication, use of an augmentative or alternative communication (AAC) system, and reading and math skill levels. The vast majority (93%) of students were served in self-contained classrooms, separate schools, or home settings, whereas only 7% were served in regular education or resource room placements. There was a significant, positive correlation between expressive communication and reading and math skill levels with increasingly inclusive classroom settings and a significant, negative correlation between use of AAC and more inclusive settings. Implications of these findings are discussed.